4.1k views
3 votes
Help me solve this question pleasee


Help me solve this question pleasee ​-example-1

1 Answer

7 votes

Answer:

I am going to let a = (p)^1/2 and b = (q)^1/2 for ease in typing

(a + b) / (1 - a) = (4 a + b) / (1 - a^2) = (4 a + b) / [(1 - a) (1 + a)]

a + b = (4 a + b) / (1 + a) multiply by (1 - a)

a + a^2 + b + b a) = 4 a + b

a + a^2 + b a = 4 a drop b on both sides

a^2 + b a = 3 a

b a = 3 a - a^2

b = 3 - a divide by a

a + b = 3

or p^1/2 + q^1/2 = 3

User Narayan Acharya
by
5.0k points